Efficacy of Bioenergetic Health Index to Predict Delirium After Major Abdominal Surgery in Elderly Patients: A Protocol for a Prospective Observational Cohort Study - Zhao, Yi; Liu, Juan; Ou, Mengchan; Hao, Xuechao (Frontiers in Medicine, 2022)
Introduction Postoperative delirium (POD) is a common disorder following surgery, which seriously threatens the quality of patients’ life, especially the older people. The multifactorial manner of this syndrome has made it hard to define an ideal method to predict individual risk. Mitochondria play a key role in the process of POD, which include inflammatory on the brain caused by surgeries and aging related neurodegeneration. As BHI (Bioenergetic Health Index) could be calculated in cells isolated from an individual’s blood to represent the patient’s composite mitochondrial statue, we hypotheses that HBI of monocytes isolated from individual’s peripheral blood can predict POD after major non-cardiac surgery in elderly patients. Methods and Analysis This is a prospective, observational single-blinded study in a single center. 124 patients aged ≥ 65 years and scheduled for major abdominal surgery (>3 h) under general anesthesia will be enrolled. Preoperative and postoperative delirium will be assessed by trained members using Confusion Assessment Method (CAM). For patients unable to speak in the ICU after the surgery, Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) will be used. All patients will undergo venous blood sampling twice to measure BHI (1–2 tubes, 5 ml/tube): before the surgery and 1 day after surgery in wards. After discharge, patients will be contacted by telephone 30 days after surgery to confirm the incidence of post-discharge complications. The severity of complications will be categorized as mild, moderate, severe or fatal using a modified Clavien-Dindo Classification (CDC) scheme. Ethics and Dissemination The study has been approved by the Ethics Committee on Biomedical Research, West China Hospital of Sichuan University, Sichuan, China (Chairperson Prof Shaolin Deng, No. 2021-502). Study data will be disseminated in manuscripts submitted to peer-reviewed medical journals as well as in abstracts submitted to congresses. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [ChiCTR2100047554].